Improvement of the Technology of Industrial Wastewater Treatment in the Mining Industry - Qizi, Panjieva Muqaddas Baxodir; Lolayevich, Shukurov Jurabek (Bumi Publikasi Nusantara, 2023)
Mining waste reduction methods include all mining processes beginning from resource distribution until the final products in the plant. For comparing and testing possibilities of mine waste reduction, a cooperation project has been set up aiming to create a transnational network with regional networks. The activities carried out on the regional and transnational level secure better access to knowledge, state-of-the-art technologies, and good practice. The study addresses all the waste management challenges and opportunities in mining industry, giving understanding all forms of extraction of natural non-renewable resources.